1985
DOI: 10.1002/ijc.2910360608
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of a hepatoma‐specific band of serum gamma‐glutamyl transferase

Abstract: Using a vertical slab electrophoretic apparatus loaded with polyacrylamide stage gel plate, we observed a total of II bands of gamma-glutamyl transferase (EC 2.3.2.2,GGT) on a gel plate and designated these GGT I-XI by order of distance beginning at the positive pole. Positive GGT II was found in 81 (90%) of 90 cases of primary hepatic carcinoma (PHC), in 9(90%) of 10 cases of secondary hepatic carcinoma (SHC), and in only 4 (3.1%) of a total of 128 cases of acute and chronic liver disease. There was one case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 13 publications
1
21
1
Order By: Relevance
“…Kuromatsu and Okuda also detected no obvious correlation between AFP and PIVKAII measured by the revised EIA kit in their HCC patients (Kuromatsu et al, 1997;Okuda et al, 1999). The sensitivity of GGTII in patients without increased AFP was about 62%, which was less than that in Xu et al's (1985) report (84.6%). All papers about GGT in the HCC diagnosis report no apparent correlation between AFP and GGTII, consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Kuromatsu and Okuda also detected no obvious correlation between AFP and PIVKAII measured by the revised EIA kit in their HCC patients (Kuromatsu et al, 1997;Okuda et al, 1999). The sensitivity of GGTII in patients without increased AFP was about 62%, which was less than that in Xu et al's (1985) report (84.6%). All papers about GGT in the HCC diagnosis report no apparent correlation between AFP and GGTII, consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 81%
“…Other researchers used polyacrylamide gel gradient electrophoresis to fractionate one to three bands of GGT specific for hepatoma with a positivity rate of only 27 -63% (Hetland et al, 1975;Kojima et al, 1980;Sawabu et al, 1983;Kew et al, 1984). In 1985, Xu reported that they had fractionated nine to 11 activity bands of GGT adopting the method of vertical slab stage electrophoresis on polyacrylamide gel (Xu et al, 1985), in which GGTII was found in the sera of all patients with hepatoma. The positive rate of GGT was 90% and no correlation was observed with AFP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18] However, the HSBs in previous studies were observed qualitatively only after gel electrophoresis separation, and the alteration of HSB concentration in different liver diseases remained unclear. The primary objective of the current study, therefore, was to establish a quantitative method of HSB activity of serum GGT in patients with liver diseases.…”
Section: I4mentioning
confidence: 97%